Delayed Presentation of Gluteal Compartment Syndrome: The Argument for Fasciotomy - John E. Lawrence; Duncan J. Cundall-Curry; Kuldeep K. Stohr (Case Reports in Orthopedics)
A male patient in his fifties presented to his local hospital with numbness and weakness of the right leg which left him unable to mobilise. He reported injecting heroin the previous morning. Following an initial diagnosis of acute limb ischaemia the patient was transferred to a tertiary centre where Computed Tomography Angiography was reported as normal. Detailed neurological examination revealed weakness in hip flexion and extension (1/5 on the Medical Research Council scale) with complete paralysis of muscle groups distal to this. Sensation to pinprick and light touch was globally reduced. Blood tests revealed acute kidney injury with raised creatinine kinase and the patient was treated for rhabdomyolysis. Orthopaedic referral was made the following day and a diagnosis of gluteal compartment syndrome (GCS) was made. Emergency fasciotomy was performed 56 hours after the onset of symptoms. There was immediate neurological improvement following decompression and the patient was rehabilitated with complete nerve recovery and function at eight-week follow-up. This is the first documented case of full functional recovery following a delayed presentation of GCS with sciatic nerve palsy. We discuss the arguments for and against fasciotomy in cases of compartment syndrome with significant delay in presentation or diagnosis.